MORAL INTELLIGENCE AND ITS RELATIONSHIP TO NEUROTICISM (MOVEMENT AGAINST OTHERS) AMONG HIGH SCHOOL STUDENTS - Assis. Doctor: Zahraa Tariq Batal (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The research aims to identify: 1- The level of moral intelligence among high school students. 2- The level of neuroticism (movement against others) among high school students. 3- The correlation between moral intelligence and neuroticism (movement against others) among high school students. The research sample amounted to (200) high school students (males and females) (scientific and literary) in (2019-2020), and the standards were applied to them electronically due to the Corona pandemic. The researcher adopted the previously prepared moral intelligence scale (Al-Awsi, 2010) which was built according to the theory of (Burba, 2001), as it consists of (49) paragraphs in its final form in a triple gradient and it is (always, sometimes, rarely) distributed into seven domains by (9) paragraphs for each field. The researcher verified that Standard characteristics of the scale are veracity and reliability. The researcher also adopted the neuroticism scale (move against others) built by (Rady, 2011) according to Horney’s theory and consisting of (40) paragraphs in the form of reportable statements distributed in five areas and with a five-fold gradation, which is (completely agree, agree, no opinion, reject Absolutely reject) The researcher also verified the psychometric properties of the scale: After analyzing the data, the following results were shown: The sample has a high level of moral intelligence, and the average scores of the sample individuals on the moral intelligence scale were statistically significant. - The sample has an average level of neuroticism (moving against others), and the average scores of the sample members on the scale of neurotic tendency (moving against others) were statistically insignificant. - The presence of a negative correlational relationship between moral intelligence and neuroticism (movement against others) among high school students. Based on the research results, the researcher recommends a set of recommendations and suggestions.